Awareness and Knowledge of Vestibular Dysfunction among Individuals with Diabetes Mellitus: A Cross-sectional Study - Uzma Abdul Wahid Shaikh; Kiran Yatin Pawar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Vestibular dysfunction is a debilitating yet under-recognised complication of Diabetes Mellitus (DM) that significantly elevates fall risk and diminishes quality of life. Clinical studies demonstrate a significant prevalence of vestibular impairment in diabetic populations; however, there is a notable deficiency of data concerning patient awareness of this relationship. Understanding this awareness gap is essential to justify the integration of vestibular screening into standard diabetes care and to develop targeted educational interventions that promote early diagnosis. Aim: To assess awareness and knowledge regarding vestibular dysfunction among individuals with chronic Diabetes Mellitus (DM) Type 1 (T1DM) and Type 2 DM (T2DM) using a validated questionnaire. Materials and Methods: This community-based cross-sectional observational study, was conducted in association with KJ Somaiya College of Physiotherapy, Mumbai, Maharashtra, India, from March 2025 to August 2025, involving 150 individuals aged 30 to 60 years. Participants were recruited using convenience sampling from KJ Somaiya Hospital (OPD and IPD) and residential communities in East Mumbai, Maharashtra, India. A validated questionnaire was used to collect data on the levels of awareness and knowledge of vestibular dysfunction in patients with DM. Microsoft Excel was used to perform descriptive statistics, and results were represented using tables and bar graphs. Results: Only 23 of the 150 participants (15.3%) were aware that diabetes may contribute to vestibular impairment. While 79 (52.7%) participants understood that dizziness is not solely attributable to hypotension or hypoglycaemia, familiarity with specific vestibular terminology was limited. Vertigo was recognised by 92 (61.3%) participants, whereas nystagmus was recognised by only 17 (11.3%). While 108 (72.0%) recognised that glycaemic control could alleviate symptoms, only 54 (36.0%) were aware of physiotherapy-based Vestibular Rehabilitation (VR). A higher level of education was significantly associated with increased awareness and knowledge scores. Conclusion: There is a substantial gap in patient awareness regarding the vestibular complications of diabetes. Awareness and knowledge levels were associated with educational status. Early screening, physiotherapy-based interventions and the integration of vestibular health education into diabetes care may reduce fall risk and improve quality of life.